(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This paper presents a prototype development for an automated control system for production checkpoints within the Industry 4.0 framework. The system integrates biometric recognition, RFID technology, and automated access control mechanisms to enhance security and efficiency. The study highlights the advantages of an event-driven model for real-time access control and system scalability. The proposed solution ensures seamless integration with enterprise control systems, reducing operational risks and improving workforce monitoring.